A model to foster and facilitate trust and trusting relationships in the nursing education context - Ellie C. van Dyk; Gisela H. van Rensburg; Elsie S. Janse van Rensburg (AOSIS, 2021)
Background: In the nursing education context, the fostering of trust and establishing trusting relationships are important facets of teaching and learning. Aim: The purpose of the study was to understand trust and trusting relationships in teaching and learning, and to develop a model to foster and facilitate trust and trusting relationships in the nursing education context. Setting: Two nursing education institutions were purposively sampled that offered a comprehensive programme in nursing. Methods: A grounded theory study was conducted with the aim to develop a model for trust and trusting relationships in teaching and learning. Purposive, convenience and theoretical sampling of participants were applied. The sample size consisted of 5 educators and 23 students at a university and 9 educators and 37 students at a public nursing education institution. Charmaz's methods were used for the data analysis. Collection and analysis of data were conducted concurrently. Results: Data of views from the educators and students on trust were synthesised. Themes identified were: professional relations, expectations of the role players in nursing education, creating a conducive teaching and learning context, and outcomes of lack of trust. From the findings, a substantive model to foster and facilitate trust and trusting relationships in nursing education was developed. Conclusion: The study contributed to understanding trust in nursing education. Recommendations focus on fostering and facilitating self-trust and trusting relationships and also on how the model could be implemented in nursing education. Contribution: Fostering and facilitating trust and trusting relationships in the nursing education context will enhance a trusting culture and contribute to the quality of teaching and learning.